Efficacy and patient-reported outcomes in advanced non-small cell lung cancer patients receiving aumolertinib as first-line therapy: a real-world study - Li, Hongxin; Zhao, Wen; Chang, Caiyun; Xuan, Tiantian; Wang, Chengjun; Zhang, Rongyu; Yang, Chuang; Wang, Jian; Yi, Cuihua; Wang, Xiuwen; Yu, Shuwen; Li, Jisheng (Frontiers in Pharmacology, 2024)
Background Aumolertinib demonstrated superior progression-free survival (PFS) and a well-tolerated toxicity profile to gefitinib in front-line treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) in the AENEAS trial. However, patient-reported outcomes (PROs) of aumolertinib have not been reported. Methods In this real-world study, efficacy was evaluated by Response Evaluation Criteria in Solid Tumors (RECIST) 1.0. PROs were evaluated using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30 (QLQ-C30) and EORTC Quality of Life lung cancer-specific module (QLQ-LC13) in advanced NSCLC patients receiving aumolertinib as initial therapy. Prespecified key symptoms were cough, hemoptysis, dyspnea, sore mouth or tongue, dysphagia, hair loss, tingling hands or feet, chest pain, arm or shoulder pain and pain of other sites. Results Totally, 33 patients were included and 23 patients had efficacy information up to Jan 2024. The median follow-up time was 264 days (interval: 36-491 days). The objective response rate and disease control rate was 65.2% and 91.3%, respectively. EORTC QLQ-LC30 showed general health status scale and functional scales increased and symptom scales decreased during aumolertinib treatment. Symptom scales assessed by EORTC QLQ-LC13 showed coughing, sore mouth or tongue, tingling hands or feet, cheat pain, arm or shoulder pain and other pain improvements were both clinically and statistically significant after 6-month aumolertinib treatment (P<0.05). Conclusions In this real-world study, aumolertinib showed comparable disease control rate and objective response rate as reported in AENEAS trial for advanced NSCLC patients with EGFR sensitizing mutation. Aumolertinib treatment improved PROs, further supported the its first-line in clinical practice.